Sarsina violascens spatial and temporal distributions affected by native vegetation strips in eucalyptus plantations - Zanuncio, José Cola; Tavares, Wagner de Souza; Ramalho, Francisco de Sousa; Leite, Germano Leão Demolin; Serrão, José Eduardo (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate spatial and temporal distributions of Sarsina violascens (Lepidoptera: Noctuidae: Lymantriinae) in two Eucalyptus cloeziana plantations, one with native vegetation strips (WNVS) and another without them (ONVS). Adults were collected with light traps, which were installed: inside an area of native vegetation (Cerrado), 100 m from the edge; at the contact zone between the native vegetation area and the E. cloeziana plantation; inside the E. cloeziana plantation, 250 m from the edge; at the central part of the native vegetation strip, around 500 m from the edge (WNVS) or in the contact zone between two E. cloeziana compartments (ONVS); and inside the E. cloeziana plantation, 500 m from the edge. The number of S. violascens adults collected was 240 in the system WNVS and 1,378 in the system ONVS. The lower number of individuals in the system WNVS was probably due to favored biological control provided by higher species richness with the use of native vegetation strips. These strips, intermingled with E. cloeziana plantations, allow a higher proportion of native forest in the landscape and can help to reduce S. violascens infestations.